Prevalence of Chronic Suppurative Otitis Media in Out Patient Department (OPD) in a District Level 250 Bedded General Hospital, Gopalganj, Bangladesh - Mahfuz, Md Sirajul Islam; A, Kabir; Haq, AHM Zahurul; Chowdhury, Allam; Taous, Ahmmad; Islam, Md Mozaharul (Bangladesh Journal of Otorhinolaryngology, 2020)
Aims: To find out the prevalence and profile of chronic suppurative otitis media (CSOM) in district level of Bangladesh. Methods: This was a prospective cross sectional study which was carried out patients of chronic suppurative otitis media attended in OPD of 250 Bedded General Hospital, Gopalganj. A total number of 200 patients of CSOM were randomly selected from OPD irrespective of sex and religion during period of July 2015 to June 2016. Age ranging 0- 60 years and person residents of Gopalganj and adjacent districts. Results: In this study 60.5% were male and 39.5%female. Male Female ratio 3:2. Majority of respondents were age group is 11 to 20 years. (36.5%). Mean age of patient 29.98 years. Maximum families 52% had monthly income of TK 10,000 to 15,000 and maximum patients were dependant (37.5%). 5- 6 family members were highest group (60%), 60% respondent lived in Kacha house, 75% lived in rural area and 35% respondents used to bath in pond. The majority of clinical features were otorrhea (100%), deafness (32%), otalgia (42%), itchy ear (10%), tinnitus (50%), odor from ear (10%) and vertigo (5%). Most of ears (90%) were tubotymponic type of CSOM and medium size perforation were maximum (32.5%). Conclusion: Prevalence of CSOM is still high in rural area of our country and community found in younger age group. Improvement of socio-demographic factors, health awareness campaign, improved health education and easy accessibility to health care facilities can reduce the incidence of disease. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 102-109